MOLECULAR CHARACTERIZATION OF INFECTIOUS BURSAL DISEASE VIRUS ISOLATED FROM BROILER AND PULLET FLOCKS IN ALGERIA - Mourad Becheur; Abdelaziz Lounas; Omar Messaoudi; Karine Oumouna-Benachour; Mustapha Oumouna (Journal of Animal and Plant Sciences, 2024)
Infectious bursal disease (IBD) or Gumboro disease is an acute, highly contagious viral disease of young chickens characterised by haemorrhagic syndrome, severe damage in the cloacal bursa, immunosuppression, and high mortality, generally at 3–6 weeks of age. The present study was performed to investigate the molecular characteristics and histopathological effects of infectious bursal disease virus (IBDV) isolated from broiler and pullet flocks in eastern and central Algeria. Fifty-five chickens collected from eleven broiler and pullet farms were investigated for IBD outbreaks over the period of 2019–2020. Only the birds with clinical signs and macroscopic lesions indicating IBD were selected for histopathological examination and molecular investigations using reverse transcription-polymerase chain reaction (RT-PCR) followed by sequencing. Except for Flock No4, all the birds in the study showed microscopic lesions of IBD. RT-PCR confirmed IBDV infection in samples from flocks No1, 2, 3, 9, 10, and 11. Using sequencing, a very virulent IBDV (vvIBDV) strain was detected in samples No10 and 11. The studied strains exhibited four conserved amino acids (222A, 256I, 294I, and 299S), characteristic of vvIBDV. According to the phylogenetic tree, the two strains in the study were closely related to previously isolated vvIBDVs and clustered together. This result may explain the frequent vaccine failure against IBD observed in broiler and pullet flocks in Algeria.
Keywords: Molecular characterization; sequencing; vvIBDV; chickens; Algeria